Validity of the Titmus Vision Screener: A Comparison with the Snellen Chart - Navasuja Kumar; Carrie Karvonen-Gutierrez; David C. Musch; Sioban Harlow; Diana Burnett; Claudia Valenzuela; Maria A. Woodward; Roni Shtein; Leslie M. Niziol; Sayoko E. Moroi (Journal of Ophthalmic Science, 2019)
Given limited knowledge regarding validity of the Titmus vision screener, we sought to compare visual acuity measurements obtained from the Titmus with that from the Snellen chart and assess the validity properties of the Titmus as a screening instrument to detect vision impairment. Visual acuity was measured in 150 participants recruited from an academic ophthalmology practice, using the Snellen chart as well as the Titmus vision screener. Visual acuities from the Titmus and Snellen were compared and validity of the Titmus vision screener was assessed by computing sensitivity and specificity. Using Snellen visual acuity as the reference standard, the sensitivity of the Titmus vision screener to detect vision impairment, defined as visual acuity worse than 20/40, was 92% (95% CI (72.5, 98.6)) and the specificity was 64% (95% CI (57.9, 70.1)). Comparisons of the precise visual acuity level revealed poor agreement between the two methods (weighted Kappa: 0.15, 95% CI (0.08, 0.21)). Visual acuities obtained from the Titmus were, on average, two lines worse than Snellen visual acuities. ((logMAR Snellen – logMAR Titmus) = - 0.19 ± 0.29, 95% confidence interval (CI) (-0.23, -0.16)). Titmus vision screener is a sensitive tool to detect visual impairment. However high false positive results and poor agreement with Snellen limits its widespread use in clinical applications.
Keywords: Titmus